Determining Frequency of Prescription, Administration and Transcription Errors in Internal Intensive Care Unit of Shahid Faghihi Hospital in Shiraz with Direct Observation Approach: Prescription, administration and transcription errors - Afsaneh Vazin,; Mitra Fereidooni, (Iranian Journal of Pharmaceutical Sciences, 2012)
Medication errors (MEs) are the most common error in ICUs. In fact, 78% of all serious errors in ICUs are due to MEs. Therefore, detecting MEs has vital significance. The goal of this study was to investigate the frequency, type and consequences of different types of errors including prescribing, transcribing and administration errors in an ICU of a large teaching hospital. Disguised direct observation method was used to detect errors. A pharmacy student observed 307 doses in 46 days of 6 h shifts. Observation data were entered in a form designed specifically for this purpose. Two hundred and fourteen MEs were identified in 307 doses. This is equivalent to 69.7% of total error. The error breakdown is as follows: administration errors 43.1%, preparation errors 24.1% and transcription errors 2.5%. Administration techniques and monitoring were determined to be the most common errors of MEs. Nearly, 89.4% of errors did not result in imminent danger to the patients. In the ICU under this study, the most common MEs were administration and prescription errors. To improve the quality of care in the ICU and reduce MEs, efforts should be directed to correct the wrong administration technique and inappropriate monitoring. The use of pharmacy department in drug preparation instead of drug preparation by nurses, using protocols for IV infusions, providing equipment and trained personnel for therapeutic drug monitoring and measuring medications level may help reduce suboptimal drug prescription and administration.